Sustainable management : a complete guide for faculty and students - Molthan-Hill, Petra (New York, NY : Routledge, 2023)
"Sustainable Management: A Complete Guide to Faculty and Students is both a core textbook, and a guide for teachers in one convenient volume. It has become a go-to for undergraduate sustainability, green and CSR teaching, and this new edition builds on the success of the last, keeping the contents up to date with this important and fast-developing area. This unique text provides comprehensive materials to support staff wanting to integrate sustainability into their teaching and provides support to effectively embed sustainability into their curriculum. The chapters also offer a starting point in developing teaching units for master's and MBA students. The material is not just useful to people in business schools, but to those involved in wider scale curriculum change, and those looking to make links between different disciplines (for example, how to teach system thinking, corporate peace-making and the crowdsourcing of sustainable solutions), with each chapter following the same easy-to-use format. This third edition includes a new chapter on climate change education, as well as thorough updates to cover changes in the field and environment, such as resilient responses to crisis, the impact of COVID on sustainable management, social justice issues, AI and blockchain. It contains over 40 ready-made workshops which enable teachers and students to integrate the Sustainable Development Goals (SDGs) into every discipline in business, including economics, operations, marketing, HR, and financial reporting. Each chapter follows the same easy-to-use format. Online Teaching Notes to accompany each chapter are available on request with the purchase of the book"--
Revised edition of The business student's guide to sustainable management, [2017]
Includes bibliographical references and index.
Keywords: Social responsibility of business